New Insights into Inflammatory Bowel Disease - Huber, Samuel (IntechOpen, 2016)
The incidence of chronic inflammatory and autoimmune diseases is steadily increasing. Inflammatory bowel disease (IBD) is one example of a chronic inflammatory disease, which primarily affects the intestine but may also affect extraintestinal organs. The exact pathogenesis of IBD is currently unknown. However, it is clear that the pathogenesis is complex, involving barrier defects, changes in the intestinal microbiome, and chronic immune activation. This book aims to summarize basic aspects of these complex interactions between barrier function, microbiome, and the immune system. Of note, there is currently no cure for IBD. However, several therapies have evolved in the last years, which are overall able to-at least temporarily-suppress IBD. These therapies and the underlying mechanism are discussed.